Fast dissolving moxifloxacin hydrochloride antibiotic drug from electrospun Eudragit L-100 nonwoven nanofibrous mats - Giram, Prabhanjan S.; Shitole, Ajinkya; Nande, Smita S.; Sharma, Neeti; Garnaik, Baijayantimala (Materials Science & Engineering C-Materials For Biological Applications, 2018)
Antimicrobial electrospun nonwoven Eudragit L-100 nanofibrous mats containing Moxifloxacin hydrochloride (MOX-HCL) were fabricated for fast dissolving drug delivery systems (DDSs) associated with wound infection. The morphological characterization of nanofibers using ESEM revealed that the average diameter of non-woven nanofibrous mats ranges 200-600 nm. The nanofiber showed cylindrical shape with crack on the surface. Differential scanning calorimetric (DSC) and Wide Angle X-ray diffraction (WAXRD) demonstrate that the drug exists in an amorphous state in the nanofibers. Nanofibrous mats were also tested for mechanical strength, contact angle, swelling assay, haemolysis and disintegration test. In vitro disintegration tests demonstrated that the dissolution of Eudragit L-100 fiber mats was within 25 s which was higher compared to the pure drug. The Eudragit nanofibers showed pH-dependent drug release profiles, with slow release at pH 1.2 and burst release (around 30 s) at pH 6.8. The in-vitro quantitative and qualitative antimicrobial assay showed that the developed Eudragit L-100 nanofibrous mats with MOX-HCL concentration of 1%, 5% and 15 wt% exhibited antibacterial activities against both gram positive (Staphylococcus aureus) and gram negative (Escherichia coli) bacteria. The invitro cytotoxicity assay using mouse fibroblast NIH/3T3 cells demonstrated significant biocompatibility of nanofiber mats. As per the results of biological evaluation, Eudragit L-100 nanofibrous mats with 1wt% MOX-HCL could be a suitable substrate for biomedical applications. Eudragit L-100 nanofibrous mats containing Moxifloxacin hydrochloride (MOX-HCL) showed immediate DDSs for localized drug release in the wound infection at slightly acidic or alkaline conditions where faster drug release rate is required for wound healing.